Surface modified hard carbon material and preparation method thereof

By introducing a hydrophilic functional cladding with high oxygen-containing functional groups on the surface of hard carbon materials, the limitations of traditional hard carbon materials in sodium ion batteries are solved, and more efficient fast charging and discharge performance and cycle stability are achieved.

CN119581525APending Publication Date: 2025-03-07GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411750078.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Due to its limited surface functional groups in sodium ion batteries, traditional hard carbon materials have limitations in electrolyte compatibility and high temperature stability, making it difficult to achieve the improvement of fast charging and discharge performance. At the same time, it is difficult to accurately control the introduction of functional groups and the protection of structures of the oxidation modification method.

Method used

By introducing a hydrophilic functional cladding layer on the surface of the hard carbon material, the polymerization reaction is carried out by using hydrophilic monomers under the action of a radical polymerization initiator to form a surface modified hard carbon material with high oxygen-containing functional groups, improving its compatibility with the electrolyte and high temperature stability.

Benefits of technology

It improves the compatibility and high-temperature cycle stability of hard charcoal materials in electrolytes, and improves its fast charging and discharge performance and rate performance in sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581525A_ABST
    Figure CN119581525A_ABST
Patent Text Reader

Abstract

The invention provides a surface modified hard carbon material and a preparation method thereof. The surface modified hard carbon material comprises a hard carbon base material and a hydrophilic functional coating layer coating the hard carbon base material, and a Raman test shows that the ID3 / IG peak area ratio in a spectrum is 1.50-3.00. The preparation method of the surface modified hard carbon material comprises the following steps: carrying out first carbonization treatment on a hard carbon precursor material to obtain a pre-carbonized material; crushing the pre-carbonized material in an airflow crushing manner to obtain fine powder; performing secondary carbonization treatment on the fine powder in an inert atmosphere to obtain a carbonized material; adding a solvent and a free radical polymerization initiator into the carbonized material, heating in a water bath, slowly adding a hydrophilic monomer, and carrying out surface polymerization reaction to obtain a hard carbon surface hydrophilic coating material; and washing and drying the hydrophilic coating material on the surface of the hard carbon. The preparation method can realize functionalization of the surface of the hard carbon material, so that the prepared surface modified hard carbon material has a hydrophilic functional coating layer, and the compatibility and high-temperature stability of the hard carbon material in an electrolyte can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon material preparation, and in particular to a surface-modified hard carbon material and a preparation method thereof. Background Art

[0002] As a new battery technology, sodium-ion batteries began to be developed in the 1970s. At first, the development of sodium-ion batteries was often overlooked due to the lack of preliminary research and competition with other advanced battery technologies such as lithium-ion batteries. In recent years, with the scarcity of lithium-ion battery material resources and the rise in battery material prices, researchers have continued to invest in research and development, and sodium-ion batteries have gradually developed.

[0003] Compared with lithium-ion batteries, sodium-ion batteries have the following advantages: ① abundant resources, low cost, and good clean recyclability of active materials; ② high safety, maintaining a low operating pressure to avoid safety issues such as overcharging, over-discharging, and endosmosis; ③ good electrochemical stability and good cycle stability; ④ huge energy storage density, suitable for high-power applications; ⑤ less environmental pollution and relatively low complexity of use. Therefore, sodium-ion batteries are a potential energy storage technology. However, sodium-ion batteries also have some problems and challenges, such as improving electrochemical stability, targeted design and synthesis of controllable high-performance materials, electrode structure design, and electrolyte optimization. In addition, the low working potential of sodium-ion batteries imposes certain restrictions on the selection of electrode materials.

[0004] Among them, hard carbon is currently the most suitable negative electrode material for sodium ion batteries. However, traditional hard carbon materials have limitations in electrolyte compatibility and high temperature stability due to their limited surface functional groups. In order to improve the surface properties, the industry has introduced hydrophilic groups on the surface of hard carbon, which are generally introduced through oxidation treatment, that is, exposing the hard carbon material to an oxidizing environment (such as air, ozone, acid treatment, etc.) to oxidize and modify the surface. The advantages of this introduction method are simple operation, no need for additional chemical reagents, and can effectively improve the hydrophilicity of hard carbon materials. The disadvantages are that the degree of oxidation is difficult to accurately control, and excessive oxidation may cause structural damage to the hard carbon material. At the same time, a variety of different functional groups may be introduced during the oxidation process, making it difficult to achieve the selective introduction of specific functional groups, and structural defects may occur during the oxidation process, resulting in an increase in the specific surface area of ​​the hard carbon material. Therefore, there is an urgent need for a modification technology or modified hard carbon material that can effectively improve the fast charge and discharge performance of hard carbon, while ensuring the remaining performance and having industrial application potential. Summary of the invention

[0005] The purpose of the present invention is to provide a surface-modified hard carbon material and a preparation method thereof. The preparation method of the surface-modified hard carbon material has a simple process and can realize the functionalization of the surface of the hard carbon material, so that the prepared surface-modified hard carbon material has a hydrophilic functional coating layer, which can improve the compatibility and high-temperature stability of the hard carbon material in the electrolyte.

[0006] To achieve the above objectives, the first aspect of the present invention provides a surface modified hard carbon material, comprising a hard carbon substrate and a hydrophilic functional coating layer coating the hard carbon substrate. According to Raman testing, the ID3 / IG peak area ratio in the spectrum is 1.50 to 3.00.

[0007] In the technical solution adopted by the present invention, the surface modified hard carbon material includes a hard carbon substrate and a hydrophilic functional coating layer coating the hard carbon substrate, and the ID3 / IG peak area ratio in the spectrum of the Raman test is 1.50 to 3.00. The ID3 / IG peak area ratio is relatively high, indicating that the surface modified hard carbon material has a high content of oxygen-containing functional groups, has a certain degree of defects, and the degree of coating of the hydrophilic functional coating layer on the surface of the hard carbon substrate is relatively high. On the one hand, the formed hydrophilic functional coating layer can improve the wettability of the hard carbon material with the electrolyte, which is conducive to the penetration of the electrolyte and the transmission of ions, that is, improve the compatibility of the hard carbon material in the electrolyte, and thus improve the ion exchange efficiency of the battery. On the other hand, causing the hydrophilic functional coating layer can appropriately reduce the specific surface area of ​​the hard carbon material, reduce the consumption of the SEI film and the double decomposition reaction of the electrolyte, thereby improving the cycle stability of the battery at high temperature, and improving the rapid charge and discharge performance and cycle performance of the hard carbon material at high rates.

[0008] As a technical solution of the present invention, the interior of the hard carbon substrate has a nano-pore structure formed by random stacking of graphite microcrystals, and the surface of the hard carbon substrate has defects and pore structures.

[0009] As a technical solution of the present invention, the hydrophilic functional coating layer is generated by a polymerization reaction of a hydrophilic monomer under the action of a free radical polymerization initiator.

[0010] As a technical solution of the present invention, the surface modified hard carbon material has a 0.2C first charge gram capacity ≥350mAh / g, a 0.2C first charge and discharge efficiency ≥88%, a 0.5C rate sodium embedding capacity ratio increase of ≥7%, and a 1.0C rate sodium embedding capacity ratio increase of ≥6%.

[0011] As a technical solution of the present invention, the surface modified hard carbon material has a Dv10 of 2 to 4 μm, a Dv50 of 4 to 10 μm, a Dv90 of 8 to 20 μm, a Dv99 of less than 40 μm, and a particle size distribution (Dv90-Dv10) / Dv50 of 1.0 to 2.5.

[0012] As a technical solution of the present invention, the specific surface area of ​​the surface modified hard carbon material is 2.0 to 5.0 m 2 / g, oxygen content is 0.10~3.00%.

[0013] The second aspect of the present invention provides a method for preparing a surface-modified hard carbon material, comprising the steps of:

[0014] ① Carrying out the first carbonization treatment on the hard carbon precursor material to obtain a pre-carbonized material;

[0015] ② crushing the pre-carbonized material by air flow crushing to obtain fine powder;

[0016] ③ subjecting the fine powder to a second carbonization treatment under an inert atmosphere to obtain a carbonized material, wherein the temperature of the second carbonization treatment is higher than that of the first carbonization treatment;

[0017] ④ Adding a solvent and a free radical polymerization initiator to the carbonized material, heating in a water bath, slowly adding a hydrophilic monomer, and then performing a surface polymerization reaction to obtain a hard carbon surface hydrophilic coating material;

[0018] ⑤ Washing and drying the hydrophilic coating material on the surface of the hard carbon.

[0019] The preparation method of the present invention first heat-treats, crushes, and carbonizes the hard carbon precursor material to obtain a hard carbon material with graphite microcrystal accumulation and defects. The defects on the surface of the material are used as active sites, and a hydrophilic functional coating layer is formed on the surface of the hard carbon material through hydrothermal heating and graft polymerization under the action of a free radical polymerization initiator, thereby improving the compatibility and high-temperature stability of the hard carbon material in the electrolyte. The preparation method performs graft polymerization on surface defects and controls the amount of specific free radical polymerization initiators and hydrophilic monomers, and can accurately control the type and density of the introduced hydrophilic functional groups, thereby achieving highly customized surface functionalization. In addition, compared with traditional oxidation methods, the surface polymerization reaction will not cause significant damage to the basic skeleton of the hard carbon material, which is beneficial to maintaining the original physical properties.

[0020] As a technical solution of the present invention, the hard carbon precursor material includes at least one of a biomass hard carbon precursor, a resin hard carbon precursor and a coal hard carbon precursor.

[0021] As a technical solution of the present invention, the temperature of the first carbonization treatment is 350-700° C., and the time of the first carbonization treatment is 0.5-6.0 h.

[0022] As a technical solution of the present invention, the air flow crushing is to use an air flow mill to drive the pre-carbonized material to collide and crush using air flow.

[0023] As a technical solution of the present invention, the Dv10 of the fine powder is 2-4.5 μm, Dv50 is 4-10.5 μm, Dv90 is 8-21 μm, Dv99 is less than 42 μm, and the particle size distribution (Dv90-Dv10) / Dv50 is 1.0-2.5.

[0024] As a technical solution of the present invention, the fine powder is purified and dried with mixed acid before the second carbonization treatment to an ash content of <0.3%, a moisture content of <10%, and a pH of ≥3.

[0025] As a technical solution of the present invention, the inert atmosphere includes at least one of nitrogen and argon.

[0026] As a technical solution of the present invention, the temperature of the second carbonization treatment is 1000-1600° C., and the time is 0.5-8.0 h.

[0027] As a technical solution of the present invention, the solvent is water.

[0028] As a technical solution of the present invention, the free radical polymerization initiator includes persulfate or azo compound.

[0029] As a technical solution of the present invention, the free radical polymerization initiator is 0.1 to 20.0% of the mass of the carbonized material.

[0030] As a technical solution of the present invention, the hydrophilic monomer accounts for 0.1 to 20.0% of the mass of the carbonized material.

[0031] As a technical solution of the present invention, the water bath heating temperature is 50 to 100° C., and the surface polymerization reaction time is 2 to 15 hours.

[0032] As a technical solution of the present invention, the washing agent used in the washing is deionized water or anhydrous ethanol, and the washing can be repeated multiple times until the pH of the filtrate is 6.5-7.5.

[0033] As a technical solution of the present invention, the drying temperature is 50-300° C., and the drying time is greater than 5 hours.

[0034] As a technical solution of the present invention, the hydrophilic monomer contains an active double bond and a hydrophilic group, and the hydrophilic group is a carboxyl group, an ester group or a hydroxyl group.

[0035] As a technical solution of the present invention, the hydrophilic monomer includes at least one of vinyl alcohol, allyl alcohol, maleic anhydride, acrylic acid and acrylic acid derivatives. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The Raman curves of Examples 1 to 6 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0037] The surface-modified hard carbon material of the present invention has the common properties of conventional hard carbon materials, and is widely used, especially suitable for use as a negative electrode material for sodium ion batteries. The surface-modified hard carbon material of the present invention is subjected to Raman testing, and the ID3 / IG peak area ratio in the spectrum is 1.50-3.00, and the D3 / IG peak area ratio is relatively high, indicating that the surface-modified hard carbon material has a high content of oxygen-containing functional groups, a certain degree of defects, and a high degree of coating of the hydrophilic functional coating layer on the surface of the hard carbon substrate.

[0038] The 0.2C first charge capacity of the surface modified hard carbon material is ≥350mAh / g. As an example, it can be but not limited to ≥350mAh / g, ≥355mAh / g, ≥360mAh / g, ≥365mAh / g, ≥370mAh / g, ≥375mAh / g, ≥380mAh / g, ≥385mAh / g, ≥390mAh / g. The 0.2C first charge and discharge efficiency of the surface modified hard carbon material is ≥88%. As an example, it can be but not limited to ≥88%, ≥89%, ≥90%, ≥91%, ≥92%, ≥93%, ≥94%, ≥95%. The 0.5C rate sodium insertion capacity ratio of the surface modified hard carbon material is increased by ≥7%. As an example, it can be but not limited to 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%. The 1.0C rate sodium insertion capacity of the surface modified hard carbon material is increased by ≥6%. As an example, it can be but not limited to 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%. The Dv10 of the surface modified hard carbon material is 2-4μm. As an example, it can be but not limited to 2μm, 3μm, 4μm. Dv50 is 4-10μm. As an example, it can be but not limited to 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm. Dv90 is 8-20μm. As an example, it can be but not limited to 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm. Dv99 is below 40 μm. As an example, Dv99 can be, but not limited to, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm, and 40 μm. The particle size distribution (Dv90-Dv10) / Dv50 is 1.0 to 2.5. As an example, it can be, but not limited to, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, and 2.5. The specific surface area of ​​the surface-modified hard carbon material is 2.0 to 5.0 m 2 / g, as an example, the specific surface area can be but is not limited to 2.0m 2 / g, 2.5m2 / g, 3.0m 2 / g, 3.5m 2 / g, 4.0m 2 / g, 4.5m 2 / g, 5.0m 2 The oxygen content is 0.10-3.00%. For example, the oxygen content may be, but is not limited to, 0.10%, 0.50%, 1.00%, 1.50%, 2.00%, 2.50%, and 3.00%.

[0039] The surface modified hard carbon material includes a hard carbon substrate and a hydrophilic functional coating layer covering the hard carbon substrate. The interior of the hard carbon substrate has a nanoporous structure formed by random stacking of graphite microcrystals, and the surface of the hard carbon substrate has a defect and pore structure. The hydrophilic functional coating layer is generated by a polymerization reaction of a hydrophilic monomer under the action of a free radical polymerization initiator.

[0040] The preparation method of the surface modified hard carbon material of the present invention comprises the following steps: ① subjecting the hard carbon precursor material to a first carbonization treatment to obtain a pre-carbonized material; ② crushing the pre-carbonized material by air flow crushing to obtain a fine powder; ③ subjecting the fine powder to a second carbonization under an inert atmosphere to obtain a carbonized material, wherein the temperature of the second carbonization is higher than that of the first carbonization; ④ adding a solvent and a free radical polymerization initiator to the carbonized material, heating in a water bath, slowly adding a hydrophilic monomer, and then conducting a surface polymerization reaction to obtain a hard carbon surface hydrophilic coating material; ⑤ washing and drying the hard carbon surface hydrophilic coating material.

[0041] Wherein, in step ①, the hard carbon precursor material includes at least one of a biomass hard carbon precursor, a resin hard carbon precursor and a coal hard carbon precursor. Further, the hard carbon precursor material includes at least one of coconut shell, walnut shell, bamboo powder, cellulose, lignin, hemicellulose, phenolic resin, polyacrylonitrile, polystyrene, polyfurfural, polyfuran resin, bituminous coal, anthracite and lignite. The temperature of the first carbonization treatment is 350-700°C. As an example, the temperature can be but not limited to 350°C, 380°C, 400°C, 430°C, 450°C, 480°C, 500°C, 530°C, 550°C, 580°C, 600°C, 620°C, 650°C, 670°C, 700°C. The time of the first carbonization treatment is 0.5 to 6.0 h. As an example, the time may be, but is not limited to, 0.5 h, 1.0 h, 1.5 h, 2.0 h, 2.5 h, 3.0 h, 3.5 h, 4.0 h, 4.5 h, 5.0 h, 5.5 h, and 6.0 h.

[0042] In step ②, the airflow mill uses an airflow mill to drive the pre-carbonized material to collide and crush. The fine powder obtained after crushing has a Dv10 of 2 to 4.5 μm, a Dv50 of 4 to 10.5 μm, a Dv90 of 8 to 21 μm, a Dv99 of <42 μm, and a particle size distribution (Dv90-Dv10) / Dv50 of 1.0 to 2.5. The fine powder obtained after crushing is then purified and dried using an acid, which may be hydrochloric acid, hydrofluoric acid, nitric acid or a mixed acid of the foregoing. Purification-drying treatment to an ash content of <0.3%, a moisture content of <10%, and a pH ≥3.

[0043] In step ③, the inert atmosphere includes at least one of nitrogen and argon. The temperature of the second carbonization treatment is 1100-1600°C. As an example, the temperature may be, but is not limited to, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C. The carbonization time is 0.5-8.0h. As an example, the time may be, but is not limited to, 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, 7.5h, 8.0h.

[0044] In step ④, the solvent is water, and the free radical polymerization initiator includes persulfate or azo compound, and the persulfate can be ammonium persulfate or potassium persulfate. The azo compound can be 2,2'-azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate. The free radical polymerization initiator is 0.1-20.0% of the mass of the carbonized material. As an example, it can be but not limited to 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 17.0%, 18.0%, 19.0%, 20.0%.

[0045] The hydrophilic monomer contains an active double bond and a hydrophilic group, and the hydrophilic group is a carboxyl group, an ester group or a hydroxyl group. Further, the hydrophilic monomer includes at least one of vinyl alcohol, allyl alcohol, maleic anhydride, acrylic acid and acrylic acid derivatives. The hydrophilic monomer is 0.1 to 20.0% of the mass of the carbonized material. As an example, it can be but not limited to 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 17.0%, 18.0%, 19.0%, 20.0%.

[0046] The temperature of the water bath heating is 50-100° C., for example, the temperature may be, but not limited to, 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., 95° C., 100° C. The time of the surface polymerization reaction is 2-15 h, for example, the time may be, but not limited to, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h.

[0047] The detergent used for washing in step ⑤ is deionized water or anhydrous ethanol, and the washing can be repeated several times until the pH of the filtrate is 6.5 to 7.5. The drying temperature is 50 to 300°C, and the drying time is greater than 5 hours. As an example, the drying can be carried out at 120°C for 12 to 36 hours, or at 100°C for 24 to 48 hours.

[0048] After drying, the surface-modified hard carbon material can be subjected to analytical tests to determine whether it is suitable for use as a negative electrode active material for a sodium ion battery. The analytical tests include, but are not limited to, electrical performance tests, rate tests, EIS impedance tests, particle size tests, specific surface area tests, iodine adsorption value tests, methylene blue adsorption value tests, tap density tests, powder compaction density tests, oxygen content tests, phase analysis tests, scanning electron microscopy tests, transmission electron microscopy tests, EDS tests, ash content tests, elemental analysis tests, magnetic foreign matter tests, true density tests, oil absorption value tests, pH value tests, powder resistivity tests, and other items.

[0049] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0050] Example 1

[0051] This embodiment is a method for preparing a surface-modified hard carbon material, which includes the following steps.

[0052] ① Weigh 5 kg of coconut shell and place it in a graphite crucible. Put the graphite crucible into a box furnace, adjust the furnace to a nitrogen atmosphere with a nitrogen flow rate of 1 L / min, adjust the heating rate to 5 ° C / min to keep the raw material at 500 ° C for 2 hours, take out the graphite crucible after cooling, and obtain about 1 kg of pre-carbonized material.

[0053] ② Use a roller device to crush the pre-carbonized material to 2mm, and then use a jet mill to crush it to a discharge particle size Dv10 of about 2μm, a particle size Dv50 of about 5μm, a particle size Dv90 of about 10μm, a particle size Dv99 of about 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 of about 1.6, to obtain about 800g of fine powder. The fine powder is placed in a beaker, and 160g of hydrochloric acid is added for acid soaking. After acid soaking for 3h, the fine powder is filtered and washed using a positive pressure filter. The pH of the washing filtrate is close to 7. The fine powder is then placed in a blast drying oven for drying to obtain 600g of hard carbon purification material.

[0054] ③ Put the hard carbon purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace to a nitrogen atmosphere, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min to keep the raw material at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain about 500g of carbonized material.

[0055] ④ Place the beaker in a water bath, control the water bath temperature at 80℃, pour 500g of carbonized material and 25g of 2,2'-azobisisobutyronitrile (AIBN) into the beaker, add 1kg of deionized water and stir until the carbonized material is evenly dispersed, then use a pipette to slowly drip 25g of vinyl alcohol into the beaker, maintain the reaction temperature at 80℃ and stir for 12h, then take out the carbonized material to obtain a hard carbon surface hydrophilic coating material.

[0056] ⑤ Use a positive pressure filter to add deionized water to the hard carbon surface hydrophilic coating material and wash it several times until the pH of the filtrate is close to 7. Then put the hard carbon surface hydrophilic coating material into a forced air drying oven and dry it at 105°C for 24 hours to obtain a hard carbon surface modified material, recorded as HC-1.

[0057] Example 2

[0058] This embodiment is a method for preparing a surface-modified hard carbon material, which includes the following steps.

[0059] ① Weigh 5 kg of coconut shell and place it in a graphite crucible. Put the graphite crucible into a box furnace, adjust the furnace to a nitrogen atmosphere with a nitrogen flow rate of 1 L / min, adjust the heating rate to 5 ° C / min to keep the raw material at 500 ° C for 2 hours, take out the graphite crucible after cooling, and obtain about 1 kg of pre-carbonized material.

[0060] ② Use a roller device to crush the pre-carbonized material to 2mm, and then use a jet mill to crush it to a discharge particle size Dv10 of about 2μm, a particle size Dv50 of about 5μm, a particle size Dv90 of about 10μm, a particle size Dv99 of about 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 of about 1.6, to obtain about 800g of fine powder. The fine powder is placed in a beaker, and 160g of hydrochloric acid is added for acid soaking. After acid soaking for 3h, the fine powder is filtered and washed using a positive pressure filter. The pH of the washing filtrate is close to 7. The fine powder is then placed in a blast drying oven for drying to obtain 600g of hard carbon purification material.

[0061] ③ Put the hard carbon purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace to a nitrogen atmosphere, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min to keep the raw material at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain about 500g of carbonized material.

[0062] ④ Place the beaker in a water bath, control the water bath temperature at 80°C, pour 500g of carbonized material and 50g of 2,2'-azobisisobutyronitrile (AIBN) into the beaker, add 1kg of deionized water and stir until the carbonized material is evenly dispersed, then use a pipette to slowly drip 50g of vinyl alcohol into the beaker, maintain the reaction temperature at 80°C and stir for 12h, then take out the carbonized material to obtain a hard carbon surface hydrophilic coating material.

[0063] ⑤ Use a positive pressure filter to add deionized water to the hard carbon surface hydrophilic coating material and wash it several times until the pH of the filtrate is close to 7. Then put the hard carbon surface hydrophilic coating material into a forced air drying oven and dry it at 105°C for 24 hours to obtain a hard carbon surface modified material, recorded as HC-2.

[0064] Example 3

[0065] This embodiment is a method for preparing a surface-modified hard carbon material, which includes the following steps.

[0066] ① Weigh 5 kg of coconut shell and place it in a graphite crucible. Put the graphite crucible into a box furnace, adjust the furnace to a nitrogen atmosphere with a nitrogen flow rate of 1 L / min, adjust the heating rate to 5 ° C / min to keep the raw material at 500 ° C for 2 hours, take out the graphite crucible after cooling, and obtain about 1 kg of pre-carbonized material.

[0067] ② Use a roller device to crush the pre-carbonized material to 2mm, and then use a jet mill to crush it to a discharge particle size Dv10 of about 2μm, a particle size Dv50 of about 5μm, a particle size Dv90 of about 10μm, a particle size Dv99 of about 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 of about 1.6, to obtain about 800g of fine powder. The fine powder is placed in a beaker, and 160g of hydrochloric acid is added for acid soaking. After acid soaking for 3h, the fine powder is filtered and washed using a positive pressure filter. The pH of the washing filtrate is close to 7. The fine powder is then placed in a blast drying oven for drying to obtain 600g of hard carbon purification material.

[0068] ③ Put the hard carbon purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace to a nitrogen atmosphere, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min to keep the raw material at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain about 500g of carbonized material.

[0069] ④ Place the beaker in a water bath, control the water bath temperature at 80°C, pour 500g of carbonized material and 100g of 2,2'-azobisisobutyronitrile (AIBN) into the beaker, add 1kg of deionized water and stir until the carbonized material is evenly dispersed, then use a pipette to slowly drip 100g of vinyl alcohol into the beaker, maintain the reaction temperature at 80°C, stir and react for 12h, then take out the carbonized material to obtain a hard carbon surface hydrophilic coating material.

[0070] ⑤ Use a positive pressure filter to add deionized water to the hard carbon surface hydrophilic coating material and wash it several times until the pH of the filtrate is close to 7. Then put the hard carbon surface hydrophilic coating material into a forced air drying oven and dry it at 105°C for 24 hours to obtain a hard carbon surface modified material, recorded as HC-3.

[0071] Example 4

[0072] This embodiment is a method for preparing a surface-modified hard carbon material, which includes the following steps.

[0073] ① Weigh 5 kg of coconut shell and place it in a graphite crucible. Put the graphite crucible into a box furnace, adjust the furnace to a nitrogen atmosphere with a nitrogen flow rate of 1 L / min, adjust the heating rate to 5 ° C / min to keep the raw material at 500 ° C for 2 hours, take out the graphite crucible after cooling, and obtain about 1 kg of pre-carbonized material.

[0074] ② Use a roller device to crush the pre-carbonized material to 2mm, and then use a jet mill to crush it to a discharge particle size Dv10 of about 2μm, a particle size Dv50 of about 5μm, a particle size Dv90 of about 10μm, a particle size Dv99 of about 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 of about 1.6, to obtain about 800g of fine powder. The fine powder is placed in a beaker, and 160g of hydrochloric acid is added for acid soaking. After acid soaking for 3h, the fine powder is filtered and washed using a positive pressure filter. The pH of the washing filtrate is close to 7. The fine powder is then placed in a blast drying oven for drying to obtain 600g of hard carbon purification material. The ash content of the hard carbon purification material is <0.1%, and the pH is close to 7.

[0075] ③ Put the hard carbon purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace to a nitrogen atmosphere, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min to keep the raw material at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain about 500g of carbonized material.

[0076] ④ Place the beaker in a water bath, control the water bath temperature at 80℃, pour 500g of carbonized material and 150g of 2,2'-azobisisobutyronitrile (AIBN) into the beaker, add 1kg of deionized water and stir until the carbonized material is evenly dispersed, then use a pipette to slowly drip 150g of vinyl alcohol into the beaker, maintain the reaction temperature at 80℃, stir and react for 12h, then take out the carbonized material to obtain a hard carbon surface hydrophilic coating material.

[0077] ⑤ Use a positive pressure filter to add deionized water to the hard carbon surface hydrophilic coating material and wash it several times until the pH of the filtrate is close to 7. Then put the hard carbon surface hydrophilic coating material into a forced air drying oven and dry it at 105°C for 24 hours to obtain a hard carbon surface modified material, recorded as HC-4.

[0078] Example 5

[0079] This embodiment is a method for preparing a surface-modified hard carbon material, which includes the following steps.

[0080] ① Weigh 5 kg of phenolic resin and put it in a graphite crucible. Put the graphite crucible into a box furnace, adjust the furnace to a nitrogen atmosphere with a nitrogen flow rate of 2 L / min, adjust the heating rate to 5 ° C / min to keep the raw material at 500 ° C for 2 hours, take out the graphite crucible after cooling, and obtain about 1 kg of pre-carbonized material.

[0081] ② Use a roller device to roll the pre-carbonized material to 1.5mm, and then use a jet mill to crush it to a discharge particle size Dv10 of about 1.5μm, a particle size Dv50 of about 4μm, a particle size Dv90 of about 8μm, a particle size Dv99 of about 11μm, and a particle size distribution (Dv90-Dv10) / Dv50 of about 1.6, to obtain about 800g of fine powder. The fine powder is placed in a beaker, and 160g of dilute nitric acid is added for acid soaking. After acid soaking for 5h, the fine powder is filtered and washed using a positive pressure filter. The pH of the washing filtrate is close to 7. The fine powder is then placed in a blast drying oven for drying to obtain 600g of hard carbon purification material.

[0082] ③ Put the hard carbon purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace to argon atmosphere, the nitrogen flow rate to 1L / min, adjust the heating rate to 5℃ / min to keep the raw material at 1200℃ for 5h, take out the graphite crucible after cooling, and get about 500g of carbonized material.

[0083] ④ Place the beaker in a water bath, control the water bath temperature at 100℃, pour 500g of carbonized material and 30g of 2,2'-azobisisobutyronitrile (AIBN) into the beaker, add 2kg of deionized water and stir until the carbonized material is evenly dispersed, then use a pipette to slowly drip 30g of vinyl alcohol into the beaker, maintain the reaction temperature at 100℃ and stir for 15h, then take out the carbonized material to obtain a hard carbon surface hydrophilic coating material.

[0084] ⑤ Use a positive pressure filter to add deionized water to the hard carbon surface hydrophilic coating material and wash it several times until the pH of the filtrate is close to 7. Then put the hard carbon surface hydrophilic coating material into a forced air drying oven and dry it at 110°C for 20 hours to obtain a hard carbon surface modified material, recorded as HC-5.

[0085] Example 6

[0086] This embodiment is a method for preparing a surface-modified hard carbon material, which includes the following steps.

[0087] ① Weigh 5kg of coconut shell and put it in a graphite crucible. Put the graphite crucible into a box furnace, adjust the furnace to a nitrogen atmosphere with a nitrogen flow rate of 1L / min, adjust the heating rate to 3℃ / min to keep the raw material at 600℃ for 1h, take out the graphite crucible after cooling, and get about 1kg of pre-carbonized material.

[0088] ② Use a roller device to crush the pre-carbonized material to 2mm, and then use a jet mill to crush it to a discharge particle size Dv10 of about 2μm, a particle size Dv50 of about 5μm, a particle size Dv90 of about 10μm, a particle size Dv99 of about 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 of about 1.6, to obtain about 800g of fine powder. The fine powder is placed in a beaker, and 160g of hydrochloric acid is added for acid soaking. After acid soaking for 3h, the fine powder is filtered and washed using a positive pressure filter. The pH of the washing filtrate is close to 7. The fine powder is then placed in a blast drying oven for drying to obtain 600g of hard carbon purification material.

[0089] ③ Put the hard carbon purified material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace to a nitrogen atmosphere, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min to keep the raw material at 1600℃ for 2h, take out the graphite crucible after cooling, and obtain about 500g of carbonized material.

[0090] ④ Place the beaker in a water bath, control the water bath temperature at 80℃, pour 500g of carbonized material and 45g of azobisisoheptanenitrile into the beaker, add 1kg of deionized water and stir until the carbonized material is evenly dispersed, then use a pipette to slowly drip 45g of acrylic acid into the beaker, maintain the reaction temperature at 80℃ and stir for 12h, then take out the carbonized material to obtain a hard carbon surface hydrophilic coating material.

[0091] ⑤ Use a positive pressure filter to add deionized water to the hard carbon surface hydrophilic coating material and wash it several times until the pH of the filtrate is close to 7. Then put the hard carbon surface hydrophilic coating material into a forced air drying oven and dry it at 105°C for 24 hours to obtain a hard carbon surface modified material, recorded as HC-6.

[0092] Comparative Example 1

[0093] This comparative example is a method for preparing a surface-modified hard carbon material, comprising the following steps.

[0094] ① Weigh 5 kg of coconut shell and place it in a graphite crucible. Put the graphite crucible into a box furnace, adjust the furnace to a nitrogen atmosphere with a nitrogen flow rate of 1 L / min, adjust the heating rate to 5 ° C / min to keep the raw material at 500 ° C for 2 hours, take out the graphite crucible after cooling, and obtain about 1 kg of pre-carbonized material.

[0095] ② Use a roller device to crush the pre-carbonized material to 2mm, and then use a jet mill to crush it to a discharge particle size Dv10 of about 2μm, a particle size Dv50 of about 5μm, a particle size Dv90 of about 10μm, a particle size Dv99 of about 13μm, and a particle size distribution (Dv90-Dv10) / Dv50 of about 1.6, to obtain about 800g of fine powder. The fine powder is placed in a beaker, and 160g of hydrochloric acid is added for acid soaking. After acid soaking for 3h, the fine powder is filtered and washed using a positive pressure filter. The pH of the washing filtrate is close to 7. The fine powder is then placed in a blast drying oven for drying to obtain 600g of hard carbon purification material.

[0096] ③ Put the purified hard carbon material into a graphite crucible, put the graphite crucible into a high-temperature atmosphere furnace, adjust the furnace to a nitrogen atmosphere, the nitrogen flow rate is 1L / min, adjust the heating rate to 5℃ / min, keep the raw material at 1600℃ for 2h, take out the graphite crucible after cooling, and get about 500g of carbonized material, recorded as HC-0.

[0097] The HC-0 to HC-6 prepared in Examples 1 to 6 and Comparative Example 1 were subjected to various performance tests on hard carbon materials. The test results are as follows: Figure 1 As shown in Table 1, the test methods are as follows.

[0098] Raman test: The Raman spectrometer is used for testing, and the obtained spectrum (such as Figure 1 As shown in the figure, there are five peaks fitted, from left to right, namely D4 (representing sp2-sp3 hybrid structure, A1g symmetry, caused by polyene-like structure), D1 (defect-induced graphite, A1g symmetry, caused by incompleteness (heteroatoms) within the microcrystal plane), D3 (short-range sp3 carbon in amorphous carbon), G (ideal graphite lattice, E2g symmetry), D2 (surface graphene layer of graphite lattice, E2g symmetry). Therefore, the ID1 / IG peak area ratio of Raman spectrum can reflect the degree of graphitization of the material, and the ID3 / IG peak area ratio can indicate the oxygen-containing functional groups in the material.

[0099] Particle size test: Malvern laser particle size analyzer MS2000 was used for testing.

[0100] Specific surface area test: measured using a Quantachrome surface area tester, NOVA2000e.

[0101] Oxygen content test: measured using LECO oxygen, nitrogen and hydrogen analyzer.

[0102] Half-cell electrical performance test: Use N-methylpyrrolidone as solvent to prepare a 6-7% polyvinylidene fluoride solution, mix HC-0 to HC-6 hard carbon materials, polyvinylidene fluoride, and conductive carbon black in a mass ratio of 90:5:5, and apply it on copper foil. Put the coated electrode into a vacuum drying oven at a temperature of 110°C and vacuum dry it for 4 hours for use, and then punch it into small discs with a diameter of 14 mm. The cells were then transferred to an argon-filled glove box and assembled into 2430-type button cells. A three-component mixed solvent of 1 mol / L NaPF6 was used as the electrolyte in the ratio of EC:DMC:EMC=1:1:1 (volume ratio). The metal sodium sheet was used as the counter electrode. A 16 μm thick U-shaped diaphragm was used as the isolation membrane. The electrochemical performance of the assembled half-cell was tested on an electrochemical detection system. The charge and discharge voltage range was 0.001-2.8 V. The test process was as follows: (1) standing for 6 h; (2) 0.2C DC TO 0 V; (3) 0.15C DC TO 0 V; (4) 0.12C DC TO 0 V; (5) 0.08C DC TO 0 V; (6) 0.06C DC TO 0 V; (7) 0.05C DC TO 0 V; (8) 0.04C DC TO 0 V; (9) 0.03C DC TO 0 V; (10) 0.02C DC TO 0V; (11) 0.015C DC TO 0V; (12) 0.012CDC TO 0V; (13) 0.01C DC TO 0V; (14) 20 microamperes DC TO 0V; (15) 10 microamperes DC TO 0V; (16) Wait for 5 minutes; (17) 0.1C DC TO 2V; (18) Wait for 5 minutes to end the test. Rate test: Assemble the battery according to the half-charge test method in the performance test, first perform 3 cycles of 0.2C formation, and then test at different rates of 0.5C and 1.0C. The test results are shown in Table 1.

[0103] Table 1 Performance test results of Examples 1 to 6 and Comparative Example 1

[0104]

[0105]

[0106] From the results in Table 1, it can be seen that by polymerizing the hydrophilic monomer under the action of a free radical polymerization initiator to form a hydrophilic functional coating layer, the specific surface area of ​​the hard carbon material can be reduced, the oxygen content and Raman ID3 / IG data can be increased, and the rate performance can be improved.

[0107] From the comparison of Examples 1 to 4 in Table 1, it can be seen that with the increase in the content of hydrophilic monomers and free radical polymerization initiators, the oxygen content gradually increases, and the Raman ID3 / IG data also generally shows an upward trend and then decreases, indicating that the degree of defects is also increasing, and the degree of polymerization coating of the corresponding grafted hydrophilic monomer on the hard carbon surface is also increasing, but the content should not be too large, otherwise the formed hydrophilic functional coating layer will be too thick, affecting the performance of the material properties. The free radical polymerization initiator and the hydrophilic monomer should not exceed 20.0% of the mass of the carbonized material.

[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A surface-modified hard carbon material, characterized in that: The invention comprises a hard carbon substrate and a hydrophilic functional coating layer of the hard carbon substrate. According to Raman test, the ID3 / IG peak area ratio in the spectrum is 1.50-3.

00.

2. The surface-modified hard carbon material according to claim 1, characterized in that: The interior of the hard carbon substrate has a nano-pore structure formed by random stacking of graphite microcrystals, and the surface of the hard carbon substrate has defects and pore structures.

3. The surface-modified hard carbon material according to claim 1, characterized in that: The hydrophilic functional coating layer is formed by a polymerization reaction of a hydrophilic monomer under the action of a free radical polymerization initiator.

4. The surface-modified hard carbon material according to claim 1, characterized in that: The surface modified hard carbon material has a 0.2C first charge gram capacity of ≥350 mAh / g, a 0.2C first charge and discharge efficiency of ≥88%, a 0.5C rate sodium embedding capacity ratio increase of ≥7%, and a 1.0C rate sodium embedding capacity ratio increase of ≥6%.

5. The surface-modified hard carbon material according to claim 1, characterized in that: The surface modified hard carbon material has a Dv10 of 2 to 4 μm, a Dv50 of 4 to 10 μm, a Dv90 of 8 to 20 μm, a Dv99 of less than 40 μm, and a particle size distribution (Dv90-Dv10) / Dv50 of 1.0 to 2.

5.

6. The surface-modified hard carbon material according to claim 1, characterized in that: The specific surface area of ​​the surface modified hard carbon material is 2.0 to 5.0 m 2 / g, oxygen content is 0.10~3.00%.

7. A method for preparing a surface-modified hard carbon material, characterized in that: Includes steps: ① Carrying out the first carbonization treatment on the hard carbon precursor material to obtain a pre-carbonized material; ② crushing the pre-carbonized material by air flow crushing to obtain fine powder; ③ subjecting the fine powder to a second carbonization treatment under an inert atmosphere to obtain a carbonized material, wherein the temperature of the second carbonization treatment is higher than that of the first carbonization treatment; ④ Adding a solvent and a free radical polymerization initiator to the carbonized material, heating in a water bath, slowly adding a hydrophilic monomer, and then performing a surface polymerization reaction to obtain a hard carbon surface hydrophilic coating material; ⑤ Washing and drying the hydrophilic coating material on the surface of the hard carbon.

8. The method for preparing a surface-modified hard carbon material according to claim 7, characterized in that: The invention comprises at least one of the following features (1) to (14): (1) The hard carbon precursor material includes at least one of a biomass hard carbon precursor, a resin hard carbon precursor and a coal hard carbon precursor; (2) The temperature of the first carbonization treatment is 350 to 700° C., and the time of the first carbonization treatment is 0.5 to 6.0 h; (3) The air flow mill uses an air flow mill to drive the pre-carbonized material to collide and crush using air flow; (4) The fine powder has a Dv10 of 2 to 4.5 μm, a Dv50 of 4 to 10.5 μm, a Dv90 of 8 to 21 μm, a Dv99 of less than 42 μm, and a particle size distribution of (Dv90-Dv10) / Dv50 of 1.0 to 2.5; (5) The fine powder is purified and dried using a mixed acid before the second carbonization treatment to a ash content of <0.3%, a moisture content of <10%, and a pH of ≥3; (6) The inert atmosphere includes at least one of nitrogen and argon; (7) The temperature of the second carbonization treatment is 1100-1600° C., and the time is 0.5-8.0 h; (8) The solvent is water; (9) The free radical polymerization initiator comprises a persulfate or an azo compound; (10) The free radical polymerization initiator is 0.1 to 20.0% of the mass of the carbonized material; (11) The hydrophilic monomer accounts for 0.1 to 20.0% of the mass of the carbonized material; (12) The water bath heating temperature is 50 to 100° C., and the surface polymerization reaction time is 2 to 15 hours; (13) The washing agent used in the washing is deionized water or anhydrous ethanol, and the washing can be repeated multiple times until the pH of the filtrate is 6.5 to 7.5; (14) The drying temperature is 50-300°C and the drying time is >5h.

9. The method for preparing a surface-modified hard carbon material according to claim 7, characterized in that: The hydrophilic monomer contains an active double bond and a hydrophilic group, and the hydrophilic group is a carboxyl group, an ester group or a hydroxyl group.

10. The method for preparing a surface-modified hard carbon material according to claim 9, characterized in that: The hydrophilic monomer includes at least one of vinyl alcohol, allyl alcohol, maleic anhydride, acrylic acid and acrylic acid derivatives.